Effect of Germination on Antioxidant Activity of Peanut Sprouts (Arachis Hypogaea) - Hayuningtyas, Afwa; Putri, Suci Eka; Rinawati, Rinawati; Khairunnas, Khairunnas; Marniati, Marniati (Universitas Teuku Umar, 2023)
Peanuts (Arachis hypogaea L.) are plant-based foods that are abundantly available in Indonesia which also have high economic value and are an essential source of protein for many people. In Aceh, peanuts are one of the leading commodities, especially in the districts of Pidie, West Aceh, Aceh Jaya, Nagan Raya, Southwest Aceh and South Aceh. Apart from being rich in protein, it also contains fibre, antioxidants, and other good health components. During germination, proteins, starches, and lipids are metabolised by enzymes. These components are used as building blocks for growth and as a source of energy for respiration. Germination has the advantage of increasing several levels of nutrients, eliminating oligosaccharides that cause flatulence, and increasing several types of vitamins. Previous research reported that soybean germination significantly increased isoflavone levels and antioxidant activity of fresh tempeh flour produced. In this study, the antioxidant activity of peanut sprouts was identified using the DPPH (2,2-diphenyl-1-picryl-hydrazine-hydrate) radical scavenging method in three different germination times. The result shows that the most optimal percentage of antioxidant activity is the 48-hour treatment (88.24%). It also shows that the germination treatment can increase the per cent of antioxidant activity compared to peanuts without germination.